The Impact of Organization Communication Strategies and Organization Commitment on Extra-Campus Member Loyalty - Ramdani, Nur; Ishanan, Ishanan; fathurrijjal, fathurrijjal (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
This study examines the impact of organizational communication strategies and organizational commitment on extra-campus member loyalty. The method used is a quantitative approach with multiple linear regression analysis involving 100 members from three organizations in Mataram. The analysis showed a significant relationship between communication strategy and member loyalty (y), with an R Square value of 56.3%. In addition, organizational commitment positively affected member loyalty, with an R Square value of 55.4%. Further analysis showed that the combination of communication strategies and organizational commitment contributed significantly to member loyalty, with an R Square value of 63.7%. These findings emphasize the importance of effective communication and commitment in increasing the loyalty of extra-campus organization members. This research is expected to provide practical recommendations for developing better communication strategies in extra-campus organizations and encourage increased member engagement and satisfaction.